Analysis on Variables Affecting the Creation of Tourist Destination Image: Case Study on Domestic Tourists Visiting Yogyakarta between 2007 to 2009 - Khairani, Khairani; Setyowardhani, Hapsari (UI Scholars Hub, 2021)
The purpose of this study is to examine the variables that affect the image creation of tourism destinations. This research is a case study on domestic tourists visiting Yogyakarta from 2007 to 2009. This research uses an exploratory and descriptive design, conducted once in one period (cross-sectional). A number of 105 domestic tourists were selected as samples by means of non-probability sampling method and snowball sampling technique. The data were analyzed using reliability and validity tests, frequency distributions, and regression analyses. Results showed that overall image was significantly constructed and affected by cognitive and affective evaluations. Cognitive evaluation was significantly affected by the types of information source from books and movies, while affective evaluation was affected significantly by social-psychological motivations. The research also proves that Yogyakarta has fulfilled the requirements to become a tourist destination; respondents showed positive feelings towards the town and also perceived the town positively.